Transcription-dependent DNA double-strand breaks and human disease - Agnese Cristini; Natalia Gromak; Olivier Sordet (Molecular & Cellular Oncology, 2020)
Accumulation of DNA damage in resting cells is an emerging cause of human disease. We identified a mechanism of DNA double-strand break (DSB) formation in non-replicating cells, which strictly depends on transcription. These transcriptional DSBs arise from the twinned processing of R-loops and topoisomerase I and may underlie neurological disorders and cancers.